Respuesta :

Answer:

x = [tex]\frac{y}{7} - \frac{4}{7}[/tex]

Step-by-step explanation:

Since it will be easier, just set "ce" as one term. Let ce = y

You are solving for the variable, x. Note the equal sign, what you do to one side, you do to the other.

Do the opposite of PEMDAS.

First, subtract 4 from both sides:

y = 7x + 4

y (-4) = 7x + 4 (-4)

y - 4 = 7x

Next, Divide 7 from both sides:

(y - 4)/7 = (7x)/7

(y - 4)/7 = x

x = (y/7) - (4/7)

Your value of x is [tex]\frac{y}{7} - \frac{4}{7}[/tex]

~

Answer:

x=ce-4/7

Step-by-step explanation:

ce = 7x +4

ce + (-4) = (7x +4) + (-4)

ce - 4 = 7 X + 4 - 4

x= ce-4/7